In Vitro Adhesion and Invasion Rates of Staphylococcus aureus Isolated from Mastitic Cows Are Modulated by the agr System and MSCRAMM Genes - Bonsaglia, Erika Carolina Romão; Rossi, Bruna Fernanda [UNESP]; Possebon, Fabio Sossai [UNESP]; Silva, Nathalia Cristina Cirone; Gonçalves, Juliano Leonel; Castilho, Ivana Giovannetti [UNESP]; Fernandes Junior, Ary [UNESP]; Santos, Marcos Veiga dos; Rall, Vera Lúcia Mores [UNESP] (MDPI, 2025)
Mastitis, an inflammatory condition of the udder, can be caused by the entry of Staphylococcus aureus, whose adhesion to the mammary epithelial cells is influenced by virulence factors such as microbial surface components recognizing adhesive matrix molecules (MSCRAMMs) and the accessory gene regulator (agr) system. Our goal was to determine the adhesion and invasion rates of S. aureus isolates from clinical (mild and moderate) and subclinical mastitis and to assess the impact of MSCRAMM genes and agr types on disease severity. Clinical isolates predominantly carried agrII (p < 0.0083) and multiple MSCRAMM genes, correlating with high adhesion capacity but reduced invasion capacity regardless of clinical severity. Remarkably, subclinical isolates, mainly agr-negative (85.7%), showed increased cellular invasion (p < 0.0001), possibly due to reduced expression of agr-mediated virulence factors. These findings contribute to the understanding of the pathogen–host dynamics in bovine mastitis and highlight the importance of both MSCRAMMs and the agr system in modulating disease severity. These insights can inform targeted interventions for mastitis prevention and treatment.
Keywords: clinical mastitis; dairy cow; mastitis severity; pathogenicity; subclinical mastitis